Selective C–H chalcogenation of thiazoles via thiazol-2-yl-phosphonium salts. Issue 27 (26th June 2020) - Zi, You; Wagner, Konrad; Schömberg, Fritz; Vilotijevic, Ivan
Abstract : Medicinally relevant substituted benzothiazoles and thiazoles are prepared under mild conditions by a regioselective C2–H chalcogenation via preparation of the phosphonium salt and the subsequent reaction with S- and Se-centered nucleophiles. Abstract : Thiazoles and benzothiazoles undergo regioselective C2–H chalcogenation via the sequence of thiazole C2-functionalization with phosphines to produce phosphonium salts which in turn react with S- and Se-centered nucleophiles to give products of C2–H chalcogenation and allow for recovery of the starting phosphine. The atom economical sequence proceeds under mild conditions and features broad scope for both the nucleophiles (electron-rich, electron-poor, sterically hindered thiols) and the various substituted benzothiazoles. The access to the substituted medicinally relevant C2-thio benzothiazoles also enables stereoselectivity improvements in the modified Julia olefinations.